Interaction in academic L2 writing: an analysis of interactional metadiscourse strategies in applied linguistics research articles - Al-mudhaffari, Musa; Supyan Hussin,; Imran Ho Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
It has been acknowledged that academic writing is not only content-oriented but also involves various rhetorical strategies that help writers project themselves on text so that the content as well as the writer’s stance can be understood. Interactional metadiscourse (MD) strategies are established to play a rhetorical role that contribute to the persuasiveness of argument. Due to the variation of rhetorical strategies across cultures, L2 writers tend to find some problems employing appropriate interactional MD strategies to express a clear stance and engage readers in the content presented. This paper examines the extent to which interactional MD strategies are employed in advanced L2 writing. To this end, 34 research articles written by Yemeni/Arab applied linguistics L2 writers were analysed. Based on Hyland (2005a), interactional MD strategies were identified via AntConc, a concordance analytical software tool. Moreover, a qualitative analysis was conducted to examine the way how advanced L2 writers use interactional MD strategies to pursue persuasive goals. The findings indicate that L2 writers tend to employ impersonal and less dialogic style in academic writing. A closer in-depth analysis indicates that the most salient interactional strategies in Yemeni L2 writing include making bare assertion as well as marking certainty of claims. They mostly tend to make assertion as they indicate research gaps and express conviction when they state findings and summarize their research. The implications of such findings could be useful for genre analysis, academic writing and L2 writing instruction.